Macrophyte assessment in European lakes: Diverse approaches but convergent views of 'good' ecological status. (November 2018) - Poikane, Sandra; Portielje, Rob; Denys, Luc; Elferts, Didzis; Kelly, Martyn; Kolada, Agnieszka; Mäemets, Helle; Phillips, Geoff; Søndergaard, Martin; Willby, Nigel; van den Berg, Marcel S.
Graphical abstract: Highlights: We harmonised nine macrophyte-based approaches for assessing lake ecological status. We established relationships between the common view and nutrient concentrations. Submerged vegetation decrease and free-floating plants increase along the status gradient. We describe indicator taxa for 'good' and 'less than good' ecological status. We establish a 'guiding image' of the macrophyte community at 'good' ecological status. Abstract: The European Water Framework Directive has been adopted by Member States to assess and manage the ecological integrity of surface waters. Specific challenges include harmonizing diverse assessment systems across Europe, linking ecological assessment to restoration measures and reaching a common view on 'good' ecological status. In this study, nine national macrophyte-based approaches for assessing ecological status were compared and harmonized, using a large dataset of 539 European lakes. A macrophyte common metric, representing the average standardized view of each lake by all countries, was used to compare national methods. This was also shown to reflect the total phosphorus (r 2  = 0.32), total nitrogen (r 2  = 0.22) as well as chlorophyll- a (r 2  = 0.35–0.38) gradients, providing a link between ecological data, stressors and management decisions. Despite differing assessment approaches and initial differences in classification, a consensus was reached on how type-specific macrophyte assemblages change across the ecological status gradient and where ecological status boundaries should lie. A marked decline in submerged vegetation, especially Charophyta (characterizing 'good' status), and an increase in abundance of free-floating plants (characterizing 'less than good' status) were the most significant changes along the ecological status gradient. Macrophyte communities of 'good' status lakes were diverse with many charophytes and several Potamogeton species. A large number of taxa occurred across the entire gradient, but only a minority dominated at 'less than good' status, including filamentous algae, lemnids, nymphaeids, and several elodeids (e.g., Zannichellia palustris and Elodea nuttallii ). Our findings establish a 'guiding image' of the macrophyte community at 'good' ecological status in hard-water lakes of the Central-Baltic region of Europe.